Meningkatkan Kemampuan Bahasa Inggris Santri Melalui Pembelajaran Interaktif di Musholla An-Nur, Gadingrejo Pasuruan - Roidatus Shofiyah; Risma A'limathus Zuriah; Saidah Fiddaroini Harun (Jurnal Kabar Masyarakat, 2025)
This study aims to improve the English language skills of santri through interactive learning at Musholla An-Nur, Gadingrejo, Pasuruan. The interactive learning method used involves technology and activity-based approaches designed to stimulate the active participation of santri in the learning process. The research was conducted from January 1 to 31, 2025, involving 30 santri selected through purposive sampling. Data were collected through observation, in-depth interviews, and questionnaires. The results show that the interactive learning method effectively enhances the English language skills of the santri, particularly in vocabulary comprehension and speaking abailities. The implications of this study are expected to contribute to the development of English language learning in non-formal environments, especially in mushollas, and encourage the use of technology in language education.